Examining the determinants of investment decision among millennials in Malaysia - Avnner Chardles Wellfren (2013)
The number of millennials in Malaysia who participate in investment shows an increasing trend year by year. Despite that, studies have shown that most millennial investors in Malaysia do not have sufficient investment knowledge and skills. Hence, this study aimed to examine the determinants of investment decisions among millennials in Malaysia. The study has determined financial literacy, financial behaviour, financial planning, digital financial literacy and social media as independent variables and investment decisions as the dependent variable. An online questionnaire was designed and distributed using non-probability purposive sampling. The study managed to collect 176 responses around Malaysia. The data was then analysed using SmartPLS ver 3.0 for structural and model assessment. The results demonstrate that financial literacy and financial behaviour do not positively influence investment decisions. Instead, digital financial literacy, social media, and financial planning positively influence investment decisions. Furthermore, financial behaviour does not mediate the relationship between financial literacy and investment decisions. Government agencies and investment providers may include these factors in the existing financial program or financial education as a means for improvement. At the same time, millennials should take the initiative to learn skills beyond simply basic finance concepts before investing. Future studies may address differences in socioeconomic as a recommendation.